1994
DOI: 10.1080/09553009414550701
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Irradiation and Spatial Memory in Mice: Investigation of Dose-response Relationship

Abstract: Pregnant CD1 mice were exposed on gestational day 18 to 250 kV X-rays at 0.1, 0.25, 0.35 and 0.5 Gy. The performances of 10 adult male offspring from each exposure condition were investigated on a spatial discrimination learning task in a radial arm maze. An impairment in the performance of this task was found which showed a correlation with dose. Compared with sham exposed control mice, performance was not significantly affected with irradiation at 0.1 Gy and was slightly but non-significantly reduced at 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Postnatal neurogenesis probably plays an important role in normal hippocampal function, [15][16][17] and IR has been demonstrated to decrease neuronal proliferation 18,19 and contribute to memory dysfunction in rodents. 20,21 Malignant cells are generally highly sensitive to IR because of their loss of growth regulation and genomic stability. However, as part of the perturbed growth regulation, most tumor cells have lost their ability to undergo apoptosis, which means that they will die through mitotic catastrophe or senescence-like permanent growth arrest upon RT.…”
Section: Introductionmentioning
confidence: 99%
“…Postnatal neurogenesis probably plays an important role in normal hippocampal function, [15][16][17] and IR has been demonstrated to decrease neuronal proliferation 18,19 and contribute to memory dysfunction in rodents. 20,21 Malignant cells are generally highly sensitive to IR because of their loss of growth regulation and genomic stability. However, as part of the perturbed growth regulation, most tumor cells have lost their ability to undergo apoptosis, which means that they will die through mitotic catastrophe or senescence-like permanent growth arrest upon RT.…”
Section: Introductionmentioning
confidence: 99%
“…These deficits are especially relevant regarding potential long-term consequences of prophylactic and lower dose of WBI prescribed to lower the incidence of brain involvement of hematological malignancies and the delayed occurrence of brain metastases in selective solid tumors. Both neurogenesis and performance in behavioral tasks that test hippocampal function decrease in a radiation dose-dependent manner (Sienkiewicz, Haylock, & Saunders, 1994). The underlying mechanisms for these effects have remained unknown, although it was suggested that changes in neuronal precursor cells in the dentate subgranular zone of the hippocampus might be involved.…”
mentioning
confidence: 99%
“…Hippocampal damage results in various behavioral alterations (Baskar and Devi 2000;Hossain and Uma Devi 2001;Sienkiewicz et al 1994). The effects of ultrasound exposure on the hippocampus and the underlying mechanisms require comprehensive exploration.…”
Section: Introductionmentioning
confidence: 99%